Photoperiodic regulation of receptacle induction in Sargassum horneri (Phaeophyceae) using clonal thalli. Issue 3 (15th April 2014) - Yoshikawa, Shinya; Kamiya, Mitsunobu; Ohki, Kaori
Summary We developed a clonal culture of Sargassum horneri to investigate the effect of photoperiod on reproduction in this species. Regenerated vegetative thalli were obtained using lateral branches excised from a thallus grown from a single embryo under short‐day conditions (SD = 10:14 h light : dark cycle). Lateral branches excised from the SD‐regenerated thallus became vegetative thalli that remained in that phase as long as they were cultured under SD. When an excised lateral branch was cultured under long‐day conditions (LD = 14:10 h light : dark cycle), it began to enter the reproductive phase while still less than 50 mm long. Induction of the reproductive phase was accompanied by a distinctive morphological change – suppression of blade formation at the apical region of the branch; elongation of branches without blades was then followed by differentiation of receptacles bearing conceptacles on their surface. Apices of receptacles were able to interconvert between reproductive and vegetative phases, as blades resprouted upon transfer from LD to SD. The critical day length for induction of receptacle formation was between 13 and 14 h; receptacle formation was also induced under SD conditions with night breaks (NBs). These results strongly suggest that reproductive regulation of S. horneri is a photoperiodic long‐day response. NBs with blue and green light were effective for reproductive induction but not with red light. This suggests that blue‐ and/or green‐light photoreceptors are involved in the photoperiodic reproductive response of S. horneri.